Serial histology and blockface images. Full mouse heart, 600 sections - Siedlecka, U; Jones, E; Gruscheski, L; Quinn, T; Kohl, P; Casero, R (Institute for Experimental Cardiovascular Medicine, University of Freiburg; Institute of Biomedical Engineering, Department of Engineering Science and Wellcome Trust Centre for Human Genetics, University of Oxford; Heart Science Centre, National Lung and Heart Institute, Imperial College London, 2017)
Mouse hearts were excised after Schedule 1 culling according to the UK Home Office guidance on the Operation of Animals (Scientific Procedures) Act of 1986, washed swiftly in 37°C normal Tyrode solution (NaCl 140 mM; KCl 5.4 mM; MgCl2 1 mM; HEPES 5 mM; Glucose 10 mM; CaCl2 1.8 mM; pH 7.4, 300±10 mOsm) containing heparin (10u/ml) and then cannulated in cold Tyrode solution with heparin in order to perfuse the coronary vasculature from the aorta. Afterwards, hearts were arrested using modified Tyrode containing elevated potassium (20 mM), fixed by coronary perfusion with 10 mL of the fast-acting Karnovsky's fixative2 (0.75% formaldehyde, 0.75% glutaraldehyde mix) and stored overnight at 4°C. Hearts then were rinsed in cacodylate buffer (3×), dehydrated by exposure to rising alcohol concentrations (8 h in 25%, followed by 1.5 h in each of 50/70/80/90% alcohol, and 3 × 1.5 h in 100% alcohol), treated with xylene (3×1.5 h), infiltrated with wax (24 h in 50% and 48 h in 100%) and embedded in form of wax blocks. Wax blocks were mounted on Leica SM2400 heavy-duty sledge-type microtome and whole hearts were serially sectioned at 10 µm thickness.